Heritage Tourism Development Strategy in Sekanak Market Area of Palembang City - Vania Okky Putri; Wiwik Dwi Pratiwi (Centre For Tourism Planning and Development, 2021)
Sekanak Market Area is one of the historical areas in Palembang City which is identical to the heritage buildings of Sultanate and Colonial. Many potential cultures and histories should be conserved by developing them as tourist destinations. It is supported by Palembang Mayor Regulation Number 48 of 2015 regarding the Arrangement Plan for Heritage Area of Palembang City. This study focuses on heritage tourism development strategy formulation based on five aspects of tourist destination development (attraction, accessibility, amenity, accommodation, and ancillary). The study utilised quantitative description method. The data collected through observation, interviews, questioner, and related official documents. The results indicate that Sekanak Market Area needs the provision, improvement, and also development. The study proposed development strategies includes: (1) Conservation, attraction, and culture-experience components development, (2) Heritage tourism facilities provision including information and interpretation, street furniture, sanitation, accommodation, parking, finance, and souvenir center, (3) Human resources improvement which covers the community development and education, (4) Sense of place improvement by raising the local wisdom, and (5) Tourism accessibility development which in addition to the arrangement also requires the formation of tourist traditional transportation with its bases.